Factors influencing the implementation of early discharge hospital at home and admission avoidance hospital at home: a qualitative evidence synthesis - Wallis, JA; Shepperd, S; Makela, P; Han, JX; Tripp, EM; Gearon, E; Disher, G; Buchbinder, R; O'Connor, D (Cochrane Collaboration, 2024)
Background Worldwide there is an increasing demand for Hospital at Home as an alternative to hospital admission. Although there is a growing evidence base on the effectiveness and cost‐effectiveness of Hospital at Home, health service managers, health professionals and policy makers require evidence on how to implement and sustain these services on a wider scale.